Prevention of Overweight in Infancy (POI.nz) study: a randomised controlled trial of sleep, food and activity interventions for preventing overweight from birth - Taylor Barry J; Heath Anne-Louise M; Galland Barbara C; Gray Andrew R; Lawrence Julie A; Sayers Rachel M; Dale Kelly; Coppell Kirsten J; Taylor Rachael W (BMC, 2011)
Abstract Background Rapid weight gain during the first three years of life predicts child and adult obesity, and also later cardiovascular and other morbidities. Cross-sectional studies suggest that infant diet, activity and sleep are linked to excessive weight gain. As intervention for overweight children is difficult, the aim of the Prevention of Overweight in Infancy (POI.nz) study is to evaluate two primary prevention strategies during late pregnancy and early childhood that could be delivered separately or together as part of normal health care. Methods/Design This four-arm randomised controlled trial is being conducted with 800 families recruited at booking in the only maternity unit in the city of Dunedin, New Zealand. Mothers are randomised during pregnancy to either a usual care group (7 core contacts with a provider of government funded "Well Child" care over 2 years) or to one of three intervention groups given education and support in addition to "Well Child" care: the Food, Activity and Breastfeeding group which receives 8 extra parent contacts over the first 2 years of life; the Sleep group which receives at least 3 extra parent contacts over the first 6 months of life with a focus on prevention of sleep problems and then active intervention if there is a sleep problem from 6 months to 2 years; or the Combination group which receives all extra contacts. The main outcome measures are conditional weight velocity (0-6, 6-12, 12-24 months) and body mass index z-score at 24 months, with secondary outcomes including sleep and physical activity (parent report, accelerometry), duration of breastfeeding, timing of introduction of solids, diet quality, and measures of family function and wellbeing (parental depression, child mindedness, discipline practices, family quality of life and health care use). This study will contribute to a prospective meta-analysis of early life obesity prevention studies in Australasia. Discussion Infancy is likely to be the most effective time to establish patterns of behaviour around food, activity and sleep that promote healthy child and adult weight. The POI.nz study will determine the extent to which sleep, food and activity interventions in infancy prevent the development of overweight. Trial Registration Clinical Trials NCT00892983 Prospective meta-analysis registered on PROSPERO CRD420111188. Available from http://www.crd.york.ac.uk/PROSPERO